Current issues - Ronquillo, Adelaida A.; Peralta, Ana Maria R.;Salcedo, Lucila;Fontanilla, Ofelia L ;Espiritu, Socorro C (Quezon City, Philippines : Katha Publishing Co, Inc., 1995)
This edition retains the format of the previous one; presenting facts and figures about each topic. We have tried to present up-to-date information on the areas discussed to ensure that the readers and students may acquire the proper perspective and insights.
Preface -- Chapter 1: Population and related issues -- Chapter 2: The Squatter problem -- Chapter 3: The Nature of human sexuality -- Chapter 4: Family planning: for a better quality of life for the Filipino -- Chapter 5: Family disorganization nature and scope -- Chapter 6: Social values and social conscience -- Chapter 7: The Nature of Graft and Corruption -- Chapter 8: The Concept of human rights -- Chapter 9: Comprehensive Agrarian Reform Program (CARP) RA no. 6657 -- Chapter 10: The Philippine tax system -- Chapter 11: Poverty in the Philippines -- Chapter 12: The Philippine health problem -- Chapter 13: Malnutrition: a serious health problem -- Chapter 14: The Concept and nature of ecology -- Chapter 15: Drug abuse: education, prevention and control -- Addendum -- References
Includes bibliographical references.
Keywords: SOCIAL PROBLEMS